Managing Rheumatoid Arthritis with Dietary Interventions - Khanna, Shweta; Jaiswal, Kumar Sagar; Gupta, Bhawna (Frontiers in Nutrition, 2017)
Self-help by means of dietary interventions can help in management of various disorders including rheumatoid arthritis (RA), a debilitating autoimmune disease. Dietary interventions necessitate a widespread appeal for both patients as well as clinicians due to factors including affordability, accessibility and presence of scientific evidences that demonstrate substantial benefits in reducing disease symptoms such as pain, joint stiffness, swelling, tenderness and associated disability with disease progression. However, there is still an uncertainty among the community about the therapeutic benefits of dietary manipulations for RA. In the present review, we provide an account of different diets and their possible molecular mechanism of actions inducing observed therapeutic benefits for remission and management of RA. We further indicate food that can be potential aggravating factor for the disease or may help in symptomatic relief. We thereafter summarize and thereby discuss various diets and food which help in reducing levels of inflammatory cytokines in RA patients that may play an effective role in management of RA following proper patient awareness. We thus would like to promote diet management as a tool that can both supplement and complement present treatment strategies for a better patient health and recovery.